EFEKTIVITAS MODEL PEMBELAJARAN TREFFINGER DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA DAN KEMAMPUAN BERFIKIR KRITIS SISWA SMA NEGERI 2 KOTA BENGKULU - Etika Prameswari; Zamzaili Zamzaili; Hanifah Hanifah; Saleh Haji (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the Effectiveness of the Treffinger Learning Model in Improving the Ability to Understand Mathematical Concepts and Critical Thinking Skills of SMA Negeri 2 Bengkulu City Students in the even semester of the 2022/2023 academic year with the research population being all students of class XI, totaling 1,284 students and a research sample of 72 students consisting of 2 classes namely class XI MIPA U as the experimental class and class XI MIPA A as the control class. The research instrument is a test of understanding mathematical concepts and critical thinking skills. Data analysis was performed using the multivariate analysis of covariance (MANCOVA) test. The results showed that there was an influence of the Treffinger learning model on understanding mathematical concepts and critical thinking skills together at 78.7%. Furthermore, the effect of the Treffinger learning model on understanding mathematical concepts is 72.3% and the influence of the Treffinger learning model on critical thinking skills is 78.6%. The average score of students in the class taught by the Treffinger learning model is higher than that of students taught by using the Scientific learning model. The average understanding of mathematical concepts in the experimental class was 80.667 and the control class was 62.5. The average critical thinking ability in the experimental class was 78.13 and in the control class was 58.76